The Effect Of Thin Capitalization And Foreign Ownership Structure On Tax Aggressiveness Moderated By The Independence Of The Commissioner - Alif Rodhiyan; Sutrisno T; Yeney Widya Prihatiningtias (Jurnal Keuangan dan Perbankan, 2022)
The paper aims to examine the effect of thin capitalization and foreign ownership structure on tax aggressiveness and the extent to which the independence of commissioners can moderate the effect of thin capitalization and foreign ownership structure on tax aggressiveness. This study uses a purposive sampling method which produces 810 observations from 240 manufacturing companies listed on the IDX from 2016 to 2020. The study was conducted using multiple regression analysis with a moderating effect (moderated regression analysis). The result of this research is thin capitalization does not have a significant effect on tax aggressiveness. but the structure of foreign ownership affects tax aggressiveness on the measurement of earnings in the form of cash. Independent commissioners significantly moderate the effect of thin capitalization and foreign ownership structure on tax aggressiveness. The influence of independent commissioners on the relationship of foreign ownership structure to tax aggressiveness is negative. indicating that the supervisory role of independent commissioners is weakened when dealing with foreign ownership.